2018
DOI: 10.3390/atmos9120466
|View full text |Cite
|
Sign up to set email alerts
|

Hot Summers: Effect of Extreme Temperatures on Ozone in Sydney, Australia

Abstract: Poor air quality is often associated with hot weather, but the quantitative attribution of high temperatures on air quality remains unclear. In this study, the effect of elevated temperatures on air quality is investigated in Greater Sydney using January 2013, a period of extreme heat during which temperatures at times exceeded 40 • C, as a case study. Using observations from 17 measurement sites and the Weather Research and Forecasting Chemistry (WRF-Chem) model, we analyse the effect of elevated temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…For HE, we could show that the more intense these events are, the higher the probability is to be accompanied with elevated ozone concentrations. This relationship is well investigated, as high air temperatures promote the formation of high ozone concentrations through precursors [35][36][37]67,68]. This effect may be time-dependent, as we could show for Berlin, that heat events lasting over more multiple days, occurred in combination with elevated ozone concentrations.…”
Section: Influence Of Ozone Onto Heat Eventsmentioning
confidence: 56%
“…For HE, we could show that the more intense these events are, the higher the probability is to be accompanied with elevated ozone concentrations. This relationship is well investigated, as high air temperatures promote the formation of high ozone concentrations through precursors [35][36][37]67,68]. This effect may be time-dependent, as we could show for Berlin, that heat events lasting over more multiple days, occurred in combination with elevated ozone concentrations.…”
Section: Influence Of Ozone Onto Heat Eventsmentioning
confidence: 56%
“…Generally, good model skill was reported with the exception of transitional conditions (periods of substantial synoptic non-stationarity or in the presence of mesoscale motions). Likewise, Utembe et al [29] evaluated W-UM2 performance in January 2013 using eight BoM-approved sites and reported better model skill than shown here in Sections 3.2-3.4. Details regarding the more extensive meteorological evaluations of the models discussed here are given in Monk et al [25].…”
Section: Campaign Overviewmentioning
confidence: 57%
“…Given the complexity of the Westmead site, and the benchmark µMB for temperature of around ±1 °C provided by Monk et al [25], all models performed acceptably. By comparison, for January 2013 Utembe et al [29] reported a temperature µMB of 0.2 °C for W-UM2 averaging over 17 sites in the Sydney region. (b) For O-CTM, simulated temperatures were occasionally noisy and the composite diurnal mean bias (T MOD -T OBS ) was consistently positive (Figure 2b).…”
Section: Evaluating Simulated Air Temperaturementioning
confidence: 98%
See 2 more Smart Citations